2011
DOI: 10.1111/j.1742-1241.2011.02818.x
|View full text |Cite|
|
Sign up to set email alerts
|

Treatment pathways for patients with atrial fibrillation

Abstract: BackgroundAtrial fibrillation (AF) is a common rhythm disorder and the most common chronic arrhythmia. AF is associated with increased morbidity and mortality (1), and, in particular, is a major independent risk factor for stroke (2), particularly in older patients. The prevalence of AF in the UK is more than 12⁄ 1000, but this increases to at least 10% in people aged 85 years and over (3) or to 16% according to recent data (4).Atrial fibrillation represents a challenging arrhythmia. A rational approach to man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…However, earlier evidence suggested that use of anticoagulants in patients with atrial fibrillation lags behind the use of antiarrhythmic drugs and ablation. As many as 20% to 80% of those at risk for stroke fail to receive recommended anticoagulant therapy, even taking into consideration the proportion of patients who have contraindications 7,[20][21][22][23][24][25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%
“…However, earlier evidence suggested that use of anticoagulants in patients with atrial fibrillation lags behind the use of antiarrhythmic drugs and ablation. As many as 20% to 80% of those at risk for stroke fail to receive recommended anticoagulant therapy, even taking into consideration the proportion of patients who have contraindications 7,[20][21][22][23][24][25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%
“…11 Literature, however, indicates that medication use does not correlate well with the stroke risk. 12 Rather, the use of anticoagulant decreases with increasing stroke risk especially among women and older patients. 13 Women with AF are particularly at increased risk of AF complications such as stroke and death compared to men.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of the International Journal of Clinical Practice, Hodgkinson et al. (10) report a retrospective longitudinal treatment analysis of a very large (but essentially contemporary) cohort of ∼68,000 AF patients from a general practice database in the United Kingdom (9). Treatment with VKAs was analyzed according to the stroke risk, as measured by CHADS 2 score (Congestive heart failure, Hypertension, Age > 75 years, Diabetes mellitus, previous Stroke/TIA), and there was no relationship between maintenance or discontinuation of VKAs during 5‐year follow‐up and the baseline risk of stroke.…”
mentioning
confidence: 99%
“…Hodgkinson et al. (10) also reported that patients with CHADS 2 = 0 and no thromboprophylaxis at baseline received such treatment for almost 70% of treatment time. Assuming that most of them initially had so‐called ‘lone’ AF, it should be emphasised that apparently lone AF might be associated with subclinical atherosclerosis or other conditions predisposing to stroke, which necessitates a regular reassessment of lone AF patients (15), and even amongst lone AF patients, the development of new cardiac diseases and older age predicted adverse outcomes, including thromboembolism (16).…”
mentioning
confidence: 99%